Flexible editing of human motion by three‐way decomposition. (9th July 2013) - He, Zhiying; Liang, Xiaohui; Wang, Jian; Zhao, Qinping; Guo, Chengyu
ABSTRACT This paper proposes a new generative model for flexible editing of human motion. Different from previous work, three intuitive factors of motion, namely, content, identity and style, can be manipulated directly with the new model. With the new generative model, motion editing can be achieved in various aspects, including transferring an unknown style from an actor to another, synthesizing other styles for an unknown actor and generating a new motion with other content. Copyright © 2013 John Wiley & Sons, Ltd.